KETAHANAN BERWIRAUSAHA, DAYA HIDUP UKM DAN KEBERLANGSUNGAN DALAM MENGHADAPI PERSAINGAN USAHA UNTUK MENCIPTAKAN SDM YANG UNGGUL - Latif, Latif; Kamaludin, Kamaludin; Sunarto, Ading (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The aim of this PKM program is to increase the role and participation of Pamulang University PSDKU Serang City in providing suggestions and solutions based on problems faced by the community, namely the lack of knowledge about management and modern business management. The activity implementation method consists of direct face-to-face meetings through training with SME business actors, using learning methods: Lecture, Discussion and Interaction. It is hoped that in the future SMEs will be managed professionally and become the mainstay of the people's economy. The packaging is still very simple and cannot provide information regarding the products being sold so that the scope of marketing is only local consumers. The object of this activity is the MSMEs of Sasahan Village, Waringinkurung District, Serang Regency. The long-term goal of PKM activities is to prepare MSMEs in Waringinkurung Village, Serang Regency, to have human resources who have insight and knowledge in the potential for managing MSMEs, such as machete craftsmen, melinjo and durian produce. In achieving this goal, there are several stages/strategies that are followed, one of which is related to increasing the insight and capabilities of human resources. There are 3 factors that must be considered regarding the causes of failure, especially in this case for SME entrepreneurs, namely: (1). Forty-five percent of SMEs fail due to a lack of understanding of basic marketing techniques (actually including management, namely marketing management). (2). Thirty-five percent fail due to weak management capabilities. (3). Twenty percent fail due to limited funding sources. The results of this training are that MSME actors are able to improve the local economy, improve the quality of local products, provide positive social impacts, increase creativity and innovation, increase entrepreneurial awareness, and increase the economic independence of the community in forming superior human resource characters